The general principles and requirements to construction of methodical learning system of mathematical logic with use of information technologies (Journal of Information Technologies in Education (ITE), 2007)
Sinko Yuri. “The general principles and requirements to construction of methodical learning system of mathematical logic with use of information technologies”. In the article the speech goes about implementation of new information technologies in process of mathematical logic learning at the Kherson State University. The general principles and requirements to construction of methodical learning system of mathematical logic with use of information technologies are considered.